Crucial functions of alpha-actinin 2 in the embryonic heart. (10th June 2022) - Gehmlich, K; Jiang, A; Wadmore, K; Hooper, C; Douglas, G; Ehler, E; Broadway-Stringer, S; Kalisch-Smith, J; Sparrow, D; Gautel, M; Davies, B; Watkins, H
Abstract: Funding Acknowledgements: Type of funding sources: Foundation. Main funding source(s): Wellcome Trust; British Heart Foundation Background/Introduction: Alpha-actinin is an integral protein of the Z-discs in heart and skeletal muscle cells, with important structural and signalling functions. Missense variants in alpha-actinin can cause inherited conditions, e.g. myopathies and cardiomyopathies. The underlying disease mechanisms are still unknown. Purpose: In order to study the disease mechanisms of an alpha-actinin missense variant, which is known to cause Hypertrophic Cardiomyopathy in human patients, a mouse model was generated. Methods: Mice carrying the alpha-actinin missense variant were generated by CRISPR-Cas9 genome editing. The heterozygous adult mice carrying the alpha-actinin variant were characterised by echocardiography and quantitative PCR. Hearts of homozygous embryos were analysed at E15.5 by high-resolution episcopic microscopy (HREM). Results: Mice carrying a single copy of the missense variant were viable and had normal appearance. Adult heterozygous mice showed no signs of cardiomyopathy on echocardiography. However, mature male mice displayed molecular signs of cardiomyopathy, such as induction of the fetal gene programme at transcript level. The attempt to generate adult mice homozygous for the variant failed: 9 breeding pairs produced 18 litters with 83 weaned pups, but no homozygous offspring. Embryonic lethality was confirmed and E15.5 was the latest stage homozygous pups were reliably found to be viable. At this timepoint, genotype distribution was within the expected Mendelian ratios. HREM of the hearts at this stage revealed increased right ventricular chamber size and decreased left atrial size, when compared to wildtype littermates. Membranous ventricular septal defects were observed in 3 out of 8 homozygous hearts. Further these embryos displayed aortic stenosis and dysplasic leaflets of the pulmonary valve. Conclusions: Heterozygous adult mice only displayed sub-clinical signs of disease. In contrast, the missense variant is embryonic lethal in the homozygous setting and leads to a range of morphological abnormalities in E15.5 hearts. Future work will identify how altered functions of alpha-actinin cause these changes.